Extra Sodiation Sites in Hard Carbon for High Performance Sodium Ion Batteries. Issue 9 (26th July 2021) - Gan, Qingmeng; Qin, Ning; Gu, Shuai; Wang, Zhenyu; Li, Zhiqiang; Liao, Kemeng; Zhang, Kaili; Lu, Li; Xu, Zhenghe; Lu, Zhouguang
Abstract: Hard carbons are promising anodes for sodium‐ion batteries (SIBs). However, the low practical capacity from limited sodiation sites impedes their applications. Herein, ultrahigh concentration of pyridine N (≈7.9%) is introduced inside hard carbon, considering that pyridine N may provide extra sodium storage sites with stable CN and CC radicals during cycling. To expose more radical sites for sodium storage, a 3D structure with a multistage pore structure is constructed through NH3 release during the pyrolyzation process. As expected, the hard carbon with extra sodiation sites exhibits an impressively high capacity of 434 mA h g −1 at 20 mA g −1, superior rate performance of 238 mA h g −1 at a current density of 5 A g −1 and a high‐capacity retention of 98.7% after 5000 cycles. The radicals induced Na‐adsorption mechanism was further explored through ex situ electron paramagnetic resonance technology, in situ Raman technology and density functional theory calculations. The results reveal that the extra sodiation sites come from the electrostatic interaction at low potentials. This work constructs a sodium ions storage model of extra radicals and provides an extended strategy to improve the electrochemical performance of SIBs anode materials. Abstract : Ultrahigh concentration of pyridine N (≈7.9%) inside hard carbon can provide extra sodium storage sites with stable CN and CC radical during cycling, which is systematically studied by electron paramagnetic resonance technology. 3D structure with a multistage pore structure is constructed to expose more radical sites for sodium storage.